Phytochemical, Nutraceutical and Pharmacological Aspects of the Philippine native Acalypha angatensis Blanco, Fl. Filip. - Regina Lourdes Hipol; Hilda Wayas; Florence Mae Bacuyag; Madonna Daquigan; Roland Hipol; Jedida Cabanlong (Indonesian Journal of Pharmacy, 2024)
The genus Acalypha has valuable species that have significant pharmaceutical applications. This study investigated the phytochemical composition and thin layer chromatography (TLC) profile, as well as the antioxidant and antibacterial activities of the ethanolic extract of Acalypha pulogensis Sagun & G.A. Levin, an endemic species in the Philippines. Qualitative phytochemical screening revealed the presence of tannins, phenolics, flavonoids, saponins, steroids, and triterpenoids. Nutrient analysis showed that potassium and calcium content were at 1499 mg/100 g and 1380 mg/100 g, respectively. The determination of the total phenolic content (TPC) showed that this species has an average of 282.24 ± 3.56 mg GAE/g and a total flavonoid content (TFC) of 36.24 ± 3.77 mg QE/g of dried extract. These values were found to be higher than those of other Acalypha species. Antioxidant activity was measured using DPPH antioxidant assay, and the extract showed a concentration-dependent radical scavenging effect with an IC50 of 34.02 µg/mL. Antibacterial activity was evaluated using various concentrations against drug-resistant Gram-positive and Gram-negative bacteria using a resazurin-based assay. The ethanolic extract exhibited substantial antibacterial activity against Enterococcus faecium (NCTC 12204) and MRSA (ATCC 33592), with a minimum inhibitory concentration (MIC) of 4 mg/mL. Higher concentrations (>20 mg/mL) were needed for inhibition of the Gram-negative strains (Klebsiella pneumoniae and Enterobacter cloacae). These results suggest that A. pulogensis has good antioxidant and antibacterial activities that support its use in traditional medicine.